Experimental Analysis of Factors Affecting the Power Output of the PV Module - Arjyadhara Pradhan; Bhagbat Panda (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Energy is the driving force in all the sectors as it acts like an index of standard of living or prosperity of the people of the country. However heavy dependence on fossil fuels leads to global warming, hence there is a need for the use of clean, sustainable, and eco friendly form of energy. Among the various types of non-conventional energy solar energy is the fundamental as it is abundant, pollution free and universally available.Even though the main input to the PV system is the solar radiation still there are other factors which affects the efficiency of the pv module. In this paper real time experiment has been conducted to analyze the effect of various factors like irradiance, temperature, and angle of tilt, soiling, shading on the power output of the pv module. Temperature is a negative factor which reduces the efficiency of the module and can be reduced by various cooling arrangements. Presence of dust particles and shading obstructs the incident solar radiations entering the panel and the effect is seen in the iv and pv curve .For better performance solar tracking at maximum power point is suggested to improve the power output of the pv module.